Gambaran status gizi dan faktor risiko kecacingan pada anak cacingan di masyarakat Dayak Meratus, Kecamatan Loksado, Kabupaten Hulu Sungai Selatan - Annida Annida; Deni Fakhrizal; Juhairiyah Juhairiyah; Budi Hairani (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2018)
Helminthiasis is a disease caused by intestinal parasite helminth with a high prevalence and spread throughout Indonesia, not deadly but secretly and slowly affect the health and productivity of patients through the decline in nutritional status. Slow and less symptom-prone effects cause the disease to be neglected among other diseases. This research is descriptive observational with cross sectional design, to know the description of nutritional status and risk factors of helminthiasis at elementary school children suffering from helminth in Meratus Dayak community, conducted in April 2017 at SDN Loksado and SDN Tanuhi, Loksado Subdistrict, Hulu Sungai Selatan Regency, South Kalimantan Province. The results showed 6.5% of helminthiasis occurred in the Dayak community in the Loksado Subdistrict. Helminthiasis consists caused by hookworm (58.33%), Enterobius (16.66), Hymenolepis (8.33%), Trichuris (8.33%), and mix infection of hookworm and enterobius (8.33%). However, this helminthiasis has not had an impact on the patient's nutritional status and progressed without symptoms, indicated by the nutritional status of patients who are mostly in the normal category until the fat. Although helminthiasis is not a deadly disease and is emergency, but the risk factor of helminthiasis in the patient can cause chronic infestation and transmission to other children. Keywords : helminthiasis, nutritional status, risk factors